United Mexican States Reducing Fuel Subsidies : Public Policy Options - World Bank (Washington, DC, 2015)
This paper analyzes the economic, distributional, and environmental impact that energy subsidy reductions and alternative compensating mechanisms might have in Mexico. To achieve that goal, author use a computable general equilibrium model of the Mexican economy. They make several important changes to the original model to build the energy subsidies (to gasoline, diesel, electricity and liquefied petroleum gas) into the benchmark and then do an array of simulations to see the effects of removing such subsidies. The report results for 2012, which is the initial year; 2018, which will be the end of the next administration; and 2024 and 2030, which represent the medium and long term, respectively. When doing the simulations, author look at possible compensation mechanisms and analyze the impact on the income groups that may be affected by the reduction of energy subsidies.